Social entrepreneurship in hospitality principles and strategies for change - Legrand, Willy; Gardetti, Miguel Angel; Nielsen, Robert Schonrock; Johnson, Colin; Ergul, Mehmet (Taylor and Francis EBA collection, 2021)
This innovative book is the first to explore social entrepreneurship in the field of hospitality, introducing students to the principles of social entrepreneurship motivation, finance, sustainability, issues and challenges, and how these can be successfully implemented in a range of hospitality settings. The hospitality industry offers a particularly fruitful framework for social entrepreneurs, partly due to the low barriers of entry and opportunities to enhance social and environmental wealth. A variety of international case studies are integrated throughout to showcase the challenges and successes of social entrepreneurship in the hospitality industry in a wide range of settings. Discussion questions, further reading suggestions and exercises at the end of each chapter help the student to explore these concepts further. Insights into the industry's role during and potentially beyond the COVID-19 crisis are offered in the concluding chapter. The is a timely addition to the literature, written by a team of highly regarded professionals and academics, and will be essential reading for all current and future entrepreneurs in the field of Hospitality Management.